Valoración económica de las actividades de recreación en el lago Cachí, Cartago, Costa Rica - Sena Jr, Francisco M. de (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) - CATIE, Turrialba (Costa Rica), 1997